Yield, quality and economics of Indian mustard (Brassica juncea L.) as influenced under different sowing date and planting geometries in irrigated condition of eastern Uttar Pradesh - Brijesh Kumar Chaudhary; Rajesh Kumar Singh; Shiv Poojan Yadav; Harsita Nayak (Journal of Oilseed Brassica, 2026)
A field experiment was carried out at Institute of Agricultural Sciences, BHU, Varanasi to assess the effect of differentsowing date and planting geometries on yield, quality and economics of Indian mustard during Rabi season of 2015-16.The experiment was laid out in split plot design having three dates of sowing viz. D1: 26th October, D2: 05th November andD3: 15th November in main plots and five planting geometry viz. S1: 30 cm × 10 cm, S2: 30 cm × 20 cm, S3: 30 cm × 30 cm, S4:45 cm × 15 cm and S5: 45 cm × 30 cm in sub plots. The results revealed significantly higher yield attributes viz. siliquaeplant-1, seed per siliquae, siliqua length and 1000 seed weight with early sown crop. Crop sown on 26th October recorded27% and 40% higher seed yield than 5th and 15th November sown crop, respectively. Similarly, the percent increase instover yield was 27% and 29% in 26th October sown crop over 5th and 15th November sown crop respectively, though thedifference between the late sown crops remained comparable. Similar trend was also followed in oil and protein yield. Interms of economics, 26th October sown crop fetched more gross returns (Rs. 61224 ha-1) and net returns (Rs. 43684 ha-1) than 5th and 15th November. Among the different crop geometry, spacing of 30 cm × 10 cm though remained at par with30 × 20 cm spacing, both recorded significantly higher yield attributes and seed yield over other spacing. The maximumoil yield (596.3 kg ha-1), protein yield (299.8 kg ha-1), gross returns (Rs. 54350 ha-1) and net returns (Rs. 36616 ha-1) wasrecorded with the spacing of 30 cm × 10 cm over others. Therefore, it would be more appropriate to sow the mustard on26th October with a spacing of 30 cm × 10 cm for maximum productivity and profitability.